Evaluation of serum CC-16 as a biomarker for COPD in the ECLIPSE cohort. Issue 12 (29th August 2008) - Lomas, D A; Silverman, E K; Edwards, L D; Miller, B E; Coxson, H O; Tal-Singer, R
Abstract : Background: Circulating levels of Clara cell secretory protein-16 (CC-16) have been linked to Clara cell toxicity. It has therefore been suggested that this protein may be a useful marker of chronic obstructive pulmonary disease (COPD). Methods: Serum CC-16 levels were measured in 2083 individuals aged 40–75 years with COPD and a smoking history of ⩾10 pack-years, 332 controls with a smoking history of ⩾10 pack-years and normal lung function and 237 non-smoking controls. Results: Serum CC-16 had a coefficient of repeatability of 2.90 over 3 months in a pilot study of 267 individuals. The median serum CC-16 level was significantly reduced in a replication group of 1888 current and former smokers with COPD compared with 296 current and former smokers without airflow obstruction (4.9 and 5.6 ng/ml, respectively; p<0.001) and 201 non-smokers (6.4 ng/ml; p<0.001). Serum levels of CC-16 were lower in current than in former smokers with GOLD stage II and III COPD but were not different in individuals with stage IV disease. Former, but not current smokers, with COPD had lower serum CC-16 levels with increasing severity of COPD (GOLD II vs GOLD IV COPD: 5.5 and 5.0 ng/ml, p = 0.006; r = 0.11 with forced expiratory volume in 1 s, p<0.001) and had significantly higher levels if they also had reversible airflow obstruction (p = 0.034). Serum CC-16 was affected by gender and age (r = 0.35; p<0.001) in subjects with COPD but not by body mass index or the presence of either chronic bronchitis or emphysema. Conclusions: Serum CC-16 levels are reduced in individuals with COPD and there is a weak correlation with disease severity in former smokers. Trial registration number: SCO104960, NCT00292552.